2011
DOI: 10.1111/j.1365-2885.2011.01334.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 3A expression and function in liver and intestinal mucosa from dexamethasone‐treated sheep

Abstract: The effects of repeated administrations of dexamethasone (DEX) (3 mg/kg/day by i.m. route for 7 days) on the gene expression profile of a cytochrome P450 (CYP) 3A28-like isoenzyme, on the expression of a CYP3A-immunoreactive protein and on CYP3A-dependent metabolic activities in sheep liver and small intestinal mucosa were evaluated in the current work. CYP 3A-dependent metabolic activities (erythromycin and triacetyl-oleandomycin N-demethylations) were assessed in microsomal fractions. The mRNA expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…To fully evaluate and understand the possible clinical impact of these findings, the interaction of butyrate and certain drugs such as erythromycin was studied. Due to its exclusive hepatic metabolism, erythromycin is among the preferred substrates for testing the metabolic activity of the CYP3A subfamily in food‐producing species (Maté et al ., ). Erythromycin alone caused an increased expression of both CYP2H1 and CYP3A37 genes, while CYP1A was not affected in vitro .…”
Section: Discussionmentioning
confidence: 97%
“…To fully evaluate and understand the possible clinical impact of these findings, the interaction of butyrate and certain drugs such as erythromycin was studied. Due to its exclusive hepatic metabolism, erythromycin is among the preferred substrates for testing the metabolic activity of the CYP3A subfamily in food‐producing species (Maté et al ., ). Erythromycin alone caused an increased expression of both CYP2H1 and CYP3A37 genes, while CYP1A was not affected in vitro .…”
Section: Discussionmentioning
confidence: 97%
“…However, the hepatic CYP‐dependent S‐oxidation of MNP was higher (around 3.7‐fold) in sheep compared to cattle (see Table ). A survey of the available bibliography showed that hepatic CYP contents are between 0.64–0.91 nmol per mg of microsomal protein in sheep (Calléja et al ., ; Maté et al ., ) and 0.65–0.81 nmol/mg in cattle (Nebbia et al ., ; Giantin et al ., ). Based on these reported CYP contents in both species, it might be possible to estimate the CYP‐dependent S‐oxidation of MNP as turnover number (nmol/min·nmol of CYP).…”
Section: Discussionmentioning
confidence: 99%
“…Dexamethasone is considered an inducer of CYP3A4[ 34 ]. In sheep small intestine, dexamethasone caused a significant enhancement of CYP3A apoprotein level in the duodenal mucosa[ 35 ]. Thus, we suggest that dexamethasone played an important role in the excellent CYP450 expression in the serum-free medium.…”
Section: Discussionmentioning
confidence: 99%